2019
DOI: 10.1590/1807-1929/agriambi.v23n2p133-137
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and flow properties of lyophilized mango pulp with maltodextrin

Abstract: The present study had as objective to determine the flow properties and behavior of lyophilized mango pulp powder as a function of different concentrations of maltodextrin. In the samples of the powders contain 5, 10 and 15% of maltodextrin the angle of effective internal friction, wall friction angle, flow index and bulk density were determined. The microstructure was evaluated by scanning electron microscopy. The freeze-dried samples are characterized as having an amorphous structure, and the drying aid used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
3
3
0
Order By: Relevance
“…Mohammed et al (2011) state that irregularities on the particles' surfaces cause an interconnection between them, increasing the resistance to flow. Afonso et al (2019) observed the same behavior in mango pulp powders, in which the highest values of FI (4.29 and 4.52) were found in those with higher concentrations of maltodextrin, 10 and 15%, respectively.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…Mohammed et al (2011) state that irregularities on the particles' surfaces cause an interconnection between them, increasing the resistance to flow. Afonso et al (2019) observed the same behavior in mango pulp powders, in which the highest values of FI (4.29 and 4.52) were found in those with higher concentrations of maltodextrin, 10 and 15%, respectively.…”
Section: Resultssupporting
confidence: 63%
“…The addition of maltodextrin to the pulp directly interfered with the wall friction angle, and it decreased with the increase in the concentration of this adjuvant for both drying processes (Table 2). Afonso et al (2019) observed the same behavior in mango pulp powders containing maltodextrin. The friction between the powder and a wall is related to the resistance to flow existing between the powder particles and the wall material.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Maciel et al (2020) classified as cohesive and easy flowing the cupuaçu pulp powders containing maltodextrin, with I f values ranging from 3.25 to 4.09. Similarly, Afonso et al (2019), in their study with mango pulp powder containing maltodextrin, classified it as easy-flowing, with I f values between 3.19 and 4.52 I f .…”
Section: Evaluation Of Sapodilla Pulp Powder Flowabilitymentioning
confidence: 99%